Possible renoprotective mechanisms of SGLT2 inhibitors - Nishiyama, Akira; Kitada, Kento (Frontiers in Medicine, 2023)
Treatment with a sodium glucose cotransporter 2 (SGLT2) inhibitor in patients with chronic kidney disease reduces the renal risk independent of changes in blood glucose concentrations and blood pressure. However, the precise mechanism responsible for this SGLT2 inhibitor-induced renoprotective effect is unclear. We have previously shown that SGLT2 inhibitors induce antihypertensive effects with decreased sympathetic nerve activity, which is associated with transient natriuresis. Furthermore, treatment with an SGLT2 inhibitor improves renal ischemia by producing vascular endothelial growth factor-a in the renal tubules. Other studies have suggested that ketone body production, changes in glomerular hemodynamics, and intrarenal metabolic changes and a reduction in oxidative stress due to decreased tubulointerstitial glucose levels may also be involved in the renoprotective effects of SGLT2 inhibitors. In this review, we summarize the mechanism responsible for the SGLT2 inhibitor-induced renoprotective effects, including our recent hypothesis regarding an “aestivation-like response,” which is a biological defense response to starvation.